Disparities in prevalence of screening/monitoring in children with intellectual and developmental disabilities: culturally sensitive provider can mitigate effects - Mudnal, Purnima S.; Chuang, Emmeline; Needleman, Jack; Rosenau, Kashia; Kuo, Alice A. (Frontiers in Education, 2024)
Introduction About one in six children in the US, about 17% of the population, have one or more intellectual or developmental disabilities. Increases in disability due to neurodevelopmental or mental health conditions have increased by 21% in the last decade. Early intervention based on developmental screening and provider-initiated monitoring can significantly improve long-term health and cognitive outcomes. This paper assesses whether differences in receipt of developmental screening or monitoring are associated with access to a high-quality primary care medical home and having a provider who shows sensitivity to a family’s customs and values among neurotypical children and children with intellectual and developmental disabilities (IDD). Methods We used cross-sectional data from the National Survey of Children’s Health (NSCH) from 2017 to 2019. The NSCH is a nationally representative, parent-completed annual survey of children under 18. Children between 9 months and 5 years with IDD (n = 2,385) and neurotypical children (n = 20,200) were included in the analysis. Results Uptake of developmental screening/monitoring in neurotypical children and children with IDD conditions was associated with belonging to minority race/ethnic backgrounds, specifically Black, Asian, and AIAN/NHPI, and single-parent households with lower incomes, being publicly insured or uninsured and not having access to a high-quality medical home. Weighted regression models showed that the odds of neurotypical children receiving developmental monitoring/screening were 53% higher when their healthcare provider always or usually demonstrated cultural sensitivity to the family’s values and customs (OR 1.53, 95% CI, 1.08–2.18, p < 0.05). For children with IDD, the odds of receipt of monitoring/screening increased by 2.1 times when the provider always/usually demonstrated an understanding of the family’s cultural norms (95% CI, 0.99–4.43, p = 0.053). Being female was significantly associated with a lack of screening/surveillance (OR 0.73, 95% CI, 0.58–0.91, p < 0.05). Discussion With the rising prevalence of children with IDD conditions, early identification of developmental delays and subsequent access to interventions are crucial steps in supporting children and children with IDD to receive preventive care, services, and reduce disparities in accessing quality care. Implementing culturally sensitive approaches can be a low-cost and effective intervention in improving rates of provider-initiated monitoring and parent-completed screening.